2016
DOI: 10.1021/acs.inorgchem.6b00832
|View full text |Cite
|
Sign up to set email alerts
|

Copper Exchange and Redox Activity of a Prototypical 8-Hydroxyquinoline: Implications for Therapeutic Chelation

Abstract: The N-truncated β-amyloid (Aβ) isoform Aβ4-x is known to bind Cu(2+) via a redox-silent ATCUN motif with a conditional Kd = 30 fM at pH 7.4. This study characterizes the Cu(2+) interactions and redox activity of Aβx-16 (x = 1, 4) and 2-[(dimethylamino)-methyl-8-hydroxyquinoline, a terdentate 8-hydroxyquinoline (8HQ) with a conditional Kd(CuL) = 35 pM at pH 7.4. Metal transfer between Cu(Aβ1-16), CuL, CuL2, and ternary CuL(NIm(Aβ)) was rapid, while the corresponding equilibrium between L and Aβ4-16 occurred slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 17 publications
2
33
1
Order By: Relevance
“…production by Cu II ‐XZH in the presence of ascorbate/O 2 ; compared to Cu II in buffer, or Cu‐peptide complexes like Cu II ‐Aβ 1‐16 or Cu II ‐α‐synuclein, the HO . production by Cu II ‐XZH was virtually absent …”
Section: Redox Chemistrymentioning
confidence: 99%
“…production by Cu II ‐XZH in the presence of ascorbate/O 2 ; compared to Cu II in buffer, or Cu‐peptide complexes like Cu II ‐Aβ 1‐16 or Cu II ‐α‐synuclein, the HO . production by Cu II ‐XZH was virtually absent …”
Section: Redox Chemistrymentioning
confidence: 99%
“…Terdendate ligands (L) such as PBT2 can bind in a 1:1 (CuL) and a distorted 5-coordinate 1:2 (CuL 2 ) form (Kenche et al, 2013), although the predominant Cu 2+ -bound form of this class of terdentate 8HQ in a biological context is predicted to be a ternary (mixed-ligand) metal complex involving His side chains of proteins and peptides (Kenche et al, 2013). While CuL and CuL 2 are not capable of generating hydroxyl radicals in the presence of the biological reductant such as ascorbate, the dominant ternary metal complexes can produce as many hydroxyl radicals as Cu(Aβ 1−x ) in vitro (Mital et al, 2016) and ROS production can be observed following addition of such 8HQs to neural stem cell cultures (Haigh et al, 2016). These observations contrast with the founding principle of therapeutic chelation (Barnham and Bush, 2014).…”
Section: Is Therapeutic Chelation Efficacious?mentioning
confidence: 99%
“…[77] The spectroscopic signatures of Cu(A [4][5][6][7][8][9][10][11][12][13][14][15][16] ) and Cu(A [11][12][13][14][15] ) used as models for the A 4-42 and A peptides are fully reminiscent of those of the Cu II parent complexes, such as Cu(DAHK) and Cu(AAH) (see Table 1). The formation of such an ATCUN motif would preclude the formation of ternary species between Cu(A 4/11-x ) and a chelating drug candidate, [106] which stands in contrast to what has been reported in the case of the A 1-x peptide. [106][107][108] …”
Section: Coordination Sitementioning
confidence: 76%
“…The formation of such an ATCUN motif would preclude the formation of ternary species between Cu(A 4/11-x ) and a chelating drug candidate, [106] which stands in contrast to what has been reported in the case of the A 1-x peptide. [106][107][108] …”
Section: Coordination Sitementioning
confidence: 76%